Analisis Sengketa Tata Ruang Dalam Pembangunan Hotel Pullman Bandung: Studi Kasus Pelanggaran Peraturan Dan Dampaknya - Jenniviera, Johana; Bestari, Qodri; Fitriani, Adila; Maryam, Salsabilla; Mahipal, Mahipal (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract This study analyzes the spatial planning dispute surrounding the construction of the Pullman Hotel in Bandung, involving the Bandung City Government and the West Java Provincial Government. The hotel development in an area designated for government office use has sparked criticism from the community and environmental organizations. The lack of oversight and unclear permitting processes are key factors in this dispute, despite the project being expected to stimulate local economic growth. This study emphasizes the importance of inter-agency coordination, transparency in the permitting process, and the strict enforcement of sanctions against spatial planning violations to prevent similar conflicts in the future. The findings provide insights into the need for synchronized spatial planning policies to ensure sustainable development. Keywords: Spatial planning dispute, Pullman Hotel Bandung, government coordination, regulatory violations. Abstrak Penelitian ini menganalisis sengketa tata ruang dalam pembangunan Hotel Pullman Bandung yang melibatkan Pemkot Bandung dan Pemprov Jawa Barat. Pembangunan hotel di kawasan yang seharusnya diperuntukkan bagi perkantoran pemerintah telah memicu kritik dari masyarakat dan organisasi lingkungan. Kurangnya pengawasan dan ketidakjelasan perizinan menjadi faktor utama sengketa ini, meskipun proyek ini diharapkan dapat mendorong pertumbuhan ekonomi lokal. Studi ini menekankan pentingnya koordinasi antarlembaga pemerintah, transparansi dalam proses perizinan, dan penegakan sanksi yang tegas terhadap pelanggaran tata ruang untuk mencegah konflik serupa di masa depan. Hasil penelitian ini memberikan wawasan mengenai perlunya sinkronisasi kebijakan tata ruang demi pembangunan berkelanjutan. Kata Kunci: Sengketa tata ruang, Hotel Pullman Bandung, koordinasi pemerintah, pelanggaran peraturan.